Exploring the social responsibility of sport organisations - Robertson, J. F. (Victoria University, 2016)
The social responsibility of an organisation is contextual and premised on the relationship that an organisation has with society. However, organisations and societies exist in variable forms. What society expects of an organisation in one context is likely to differ in another context. Despite extensive development in management literature, the view that all organisations possess responsibilities has rarely extended beyond commercial contexts. For example in the sport industry, community sport organisations are rarely considered to have responsibilities beyond their voluntary non-profit nature. In this thesis the sport sector was used as a lens to investigate this phenomenon given the variety of different organisational forms that make-up the sector. The purpose of this thesis was to explore how organisational responsibility was perceived between and within three archetypal sport organisations. Each archetype represented an organisational field and neo-institutional theory was applied to underpin the differences between these fields. Three archetypal organisations were developed as conceptual tools based on document analysis and available reports: a community sport organisation (CSO), a national sport organisation (NSO) and an elite sport organisation (ESO). A global panel of experts was selected from sport management and sociology academics and national sport organisation managers. The expert panel consisted of 56 experts from 12 countries, 33 were academics and 23 were managers in NSOs. The Delphi method was used to determine consensus during three successive survey iterations. Each consecutive survey aimed to build consensus amongst the expert panel regarding the perceived importance of social responsibility issues in each archetype. The analysis occurred in two stages. Between organisation differences were analysed using repeated measures analyses of variance. Internal differences were determined based on how important the expert group perceived the issue to be to the organisation. The results indicated that the perception of organisational responsibility varied between archetypes. In each organisation, financial and legal responsibilities were highly important. However, anti-corruption and staff training (ESO, NSO) and inclusive participation (VSO, NSO) were only identified as important in two organisational types. Winning (ESO), social capital and community cohesion (CSO), and ethical leadership (NSO) were identified as important only in one archetype. Each of the three archetypes was perceived to have identifiable and multiple responsibilities to society. The national sport organisation had the highest perceived social responsibility (23 issues), followed by the community sport organisation (17 issues) and the elite sport organisation (13 issues). This is a new finding in the sport and social responsibility field, and marks an extension of the current knowledge concerning the social responsibility concept from corporations to the broader classification of organisations. Extending this finding further, social responsibility was perceived to be contingent on what the organisation is (constitutionally), what the organisation does (its product and services) and the position it occupies in society (within a given institutional environment). In sport management the idea that organisations have a responsibility to society is predominately investigated from the perspective of corporate social responsibility (CSR). "Corporate" and "social" qualifiers limit the conceptual focus to a narrow set of highly commercial organisational forms and a specific type of "social" responsibility. An unintended consequence of this has been that responsibility discourse remains concentrated within the corporate paradigm, instead of a broad expectation of all organisations. For theory, the diversity of organisational types within the sport industry may offer a context that broadens our understanding of (social) responsibility from the limited focus of corporate entities to a continuum of organisations ranging from non-profit to profit driven. For practice, it is recommended that the results of this research are used in conjunction with current social responsibility approaches to help frame (or benchmark) the actions of sport organisations against social expectations within specific organisational contexts.